Drainage Tube Placement May Not Be Necessary During Endoscopic Thyroidectomy Bilateral Areola Approach: A Preliminary Report - Chen, Yukai; Wang, Chengchen; Bai, Binglong; Ye, Mao; Ma, Junjie; Zhang, Jingying; Li, Zhiyu (Frontiers in Surgery, 2022)
Background The endoscopic thyroidectomy bilateral areola approach (ETBAA) improved cosmetic outcomes significantly and is now widely applied. The usage of drainage tubes is controversial in conventional open thyroidectomy (COT), but studies about drainage placement decisions during ETBAA are still limited. This study aimed to determine the feasibility of having no drainage tube applied during ETBAA on patients with papillary thyroid carcinoma. Methods The clinical data of patients undergoing ETBAA from July 2018 to May 2021 was retrospectively collected. The patients were divided into two groups based on drain placement: no-drain and drain. The two groups were matched at a ratio of 1:1. Fifty-five patients from each group were finally included. Postoperative complications and follow-up data were compared between the two groups. Results No significant difference was observed between the two groups in the incidence of postoperative complications, including hemorrhage, surgical site infection, and subcutaneous seroma. Compared with the drain group, the operation time of the no-drain group was significantly shorter [(107.75 ± 24.59) min vs. (119.91 ± 34.05) min, P < 0.05]. The total and postoperative hospital stay was significantly shorter in the no-drain group [(2.40 ± 0.71) days vs. (4.78 ± 1.33) days, P < 0.001, (2.04 ± 0.19) days vs. (2.15 ± 0.36) days, P < 0.05], and the costs of surgical consumables were also significantly lower [(6,820.83 ± 164.29) CNY vs. (7,494.13 ± 216.7) CNY, P < 0.05]. The postoperative pain score of the no-drain group was significantly lower than the drain group [(1.58 ± 0.63) vs. (1.89 ± 0.76), P < 0.05]. Conclusions No drainage applied during ETBAA on papillary thyroid carcinoma is safe and feasible. This practice does not increase the risk of postoperative complications, but it does shorten the operation time and hospital stay, as well as reduce medical costs. Furthermore, it alleviates the suffering of patients.